Family Experiences with Patient Care Using Ventilators in the ICU - Septa Permana; Sri Hendrawati; Aam Amaliah; Lili Sali; Mardiana Mochamad Ramdan (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Family members of patients receiving mechanical ventilation in the Intensive Care Unit (ICU) often experience significant emotional and psychological distress. The highly technological environment, limited patient access, and uncertainty regarding prognosis can profoundly affect family experiences and coping processes. This study aimed to explore family experiences during ICU care for patients receiving ventilator support. A qualitative descriptive study was conducted using Focus Group Discussions (FGDs) involving six family members of mechanically ventilated patients in the ICU of Welas Asih Regional General Hospital. Participants were selected using purposive sampling. Data were analyzed using thematic analysis to identify recurring patterns and meanings in family experiences. Five major themes emerged: (1) emotional shock at the initiation of ventilator use, characterized by fear, anxiety, sadness, and trauma; (2) uncertainty and psychological burden related to unclear diagnosis, limited patient interaction, and lack of regular information; (3) generally positive communication with healthcare professionals, though families desired more structured and routine updates; (4) firm hopes for patient recovery, rapid clinical response, and humane care; and (5) the need for comprehensive support, including emotional, informational, spiritual, social, and financial support. Family experiences during ventilator-assisted ICU care are complex and multidimensional. Implementing a comprehensive family-centred care approach, particularly through structured communication and holistic family support, is essential to improve family well-being and the quality of critical care services.